Effect of Sardina pilchardus oil on alloxan-induced diabetic rats. (1st January 2016) - BelHadj, Sahla; Hentati, Olfa; Baccouch, Noura; Ben Salah, Hichem; Boudaouara, Tahia; Ben Hadj, Ayda; Allouch, Noureddine; El Feki, Abdel Fattah
Abstract: The purpose of this study was to prevent or to delay the onset of diabetes-related complications, by using a natural marine resource, Sardina pilchardus oil, administrated to alloxan-induced diabetic rats showing hyperglycemia and hyperlipidemia. Gas chromatography–mass spectrometry analysis of the sardine oil detected 18 constituents. The major ones were n-3 highly unsaturated fatty acids among which are docosahexaenoic acid (25.09%) and eicosapentaenoic acid (19.61%). Sardine oil inhibited the α-amylase activity in rats' sera (26.82%) and thus improved glycemia (54%). The supplement of this oil protected the β-cells from death and damage, significantly decreased total triglycerides, total cholesterol and LDL-cholesterol concentrations in diabetic rats' sera and increased the HDL-cholesterol level. Gavage administration of this oil to rats protected the liver and kidney functions by reducing the aspartate transaminase, alanine transaminase and phosphatase alkaline activities, and by decreasing creatinine, urea and uric acid levels.